PENGARUH ASPEK KEPRIBADIAN PADA EFEKTIVITAS PEMBERIAN KREDIT - Suyantari, Putu Indah; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.03.TAHUN 2015, 2015)
The aspects of personality is one of the important factors that determine performance of an analyst in analyzing credit. Lending must be effective in order to avoid an inflation and collapse of the real sector. The purpose of this research is to obtain empirical evidence the aspect of personality such as Machiavellian personality, organizational commitment, and locus of control on the lending effectiveness. Data analysis techniques are multiple linier regression analysis. The results of research prove that the higher Machiavellian personality and locus of control of external causes the level of effectiveness of loans lower. The higher organizational commitment and internal locus of control causes the level of effectiveness on the higher loans. Key Words: Machiavellian personality , organizational commitment, locus of control, lending effectivity